Isolation of putative next-generation probiotics from selected pickled fruits in malaysia - Siti Munirah, Musa (2023)
Pickling is a preservation technique that reduces fruit spoilage and prevents contamination by pathogenic organisms. As a traditional preservation method, pickling does not require the fruit to be completely sterile before it is fermented in sugar or salt brines. Common microorganisms such as lactic acid bacteria, Micrococcaceae, Bacilli, yeast, and filamentous fungi play a pivotal role in the pickling that improve fruit end products in term of taste, colour, flavour, texture, and nutritional value. With the remarkable advances in high-throughput sequencing technologies, a novel strategy for detecting, identifying, and monitoring microbes in the food-making process are becoming possible. The microbiome, comprising microorganisms and their genes in the pickling process, can be studied to assess the impact of microbes on food safety. Generally, this study was designed to identify microbial communities at different time points of unfermented pickles. Then, the putative next-generation probiotics were isolated from the pickle fruits and evaluated phenotypically and genotypically. The first objective of this study was to profile the microbial community via the independent-culture method, targeting to avoid bias in microbial identification, where the total DNAs were extracted directly from the pickle’s brines at one-week and four-month time points and identified through amplicon sequencing by targeting the V3-region of the 16S rRNA gene to determine bacterial communities. Our observation of a greater bacterial variety in the four-month samples compared to the one-week samples is significant, indicating a dynamic microbial environment during pickling. Among the bacteria abundant in one-week samples are those from the genus Anoxybacillus_A, which is known to be thermophilic bacteria. The optimum culturable temperature is between 45 and 60 °C. On the other hand, in the four-month-old samples, the species Paenibacillus glucanolyticus shows the highest abundance in salt solution, which is well known as an endospore-forming bacteria. The second objective was conducted based on data where the potential microbes from pickle fruits that are conceivable for use as putative next-generation probiotics were isolated. The culture-dependent method was applied to obtain a single pure colony. Six different colonies were isolated and identified to be a member of the taxonomic order of Bacilales using Sanger sequencing. Finally, two bacteria with unique characteristics were selected for whole-genome sequencing for the next objective. The genera Anoxybacillus sp. nov. and Paenibacillus sp. nov. were considered novel species compared to other near branch species constructed using autoMLST server and type strain genome server (TYGS). These bacteria were also tested for morphology and chemotaxonomy analysis to understand their potential as next-generation probiotics. Anoxybacillus sp. nov. was able to survive in a high temperature up to 60°C. At the same time, Paenibacillus sp. nov. was a spore-forming bacteria that may be able to survive in harsh conditions. In conclusion, these two microbes might be putative next-generation probiotics as they are not pathogenic and have a unique characteristics that could be useful for future food biotechnology applications.